A model with combined viral and metabolic factors effectively predicts HBeAg status under long term entecavir therapy: a prospective cohort study. Issue 1 (December 2015) - Liu, Fen; Zou, Feng; Wang, Xiwei; Hu, Huaidong; Hu, Peng; Ren, Hong
Abstract Background & Aim The aim was to extract factors from virologic and biochemical profiles at baseline and 24 weeks of treatment to predict HBeAg seroconversion in patients treated with ETV. Methods HBeAg positive chronic hepatitis B patients receiving ETV naïve-treatment were enrolled. HBV DNA, ALT, and serological markers were prospectively monitored every 6 months for 240 weeks. The cumulative rates of virologic response (VR), biochemical response (BR), and HBeAg seroconversion were determined, and potential predictors for HBeAg seroconversion were identified through uni/multivariate analysis. Result Two hundred twenty nine patients were eligible for this study. The cumulative rates of VR, BR, and HBeAg seroconversion at 240 weeks were 88.4 %, 100 %, and 36.7 %, respectively. Multivariate analysis showed that HBV DNA (OR, 2.8, p = 0.003), ALT (OR, 2.6, p = 0.005) at baseline, undetectable HBV DNA within 24 weeks (OR = 3.2, p < 0.001), and body mass index (BMI) ≥24kg/m2 (OR = 0.038, p = 0.013) were associated with HBeAg seroconversion. A prediction model for probability of HBeAg seroconversion was constructed. Patients can be classified into high (>40 %), intermediate (20–40 %), or low (≤20 %) groups based on the calculated probability of HBeAg seroconversion. The cumulative rates of HBeAg seroconversion were different among the three groups (p < 0.001). About 58 % patients in the high probability group achieved HBeAg seroconversion while almost 90 % patients within the low group remained HBeAg positive. Conclusion A combination of HBV DNA, ALT and BMI values at baseline, and undetectable HBV DNA level within 24 weeks can predict HBeAg seroconversion. Both viral and metabolic factors likely determine HBeAg status with ETV treatment. Trial registration CTR20132358